Occupational burnout and the sense of coherence among pediatric nurses - Zaczyk, Iwona (Polish Journal of Public Health, 2010)
Aim. The aim of this study was to assess the level of burnout and the sense of coherence in pediatric nurses. Material and methods. The study was conducted in 2009 and the Maslach Burnout Inventory as well as the SOC-29 questionnaire in a group of 89 nurses from pediatric units. A statistical analysis was performed with the use of the student t-test in correlation to the Pearson correlation coefficient. Conclusions. The study showed that the subjects experienced a relatively low degree of occupational burnout while, at the same time, there was a high level of SOC. Moreover, there was a significant statistical correlation between the sense of coherence and a professional burnout. There were no differences when it came to professional burnout and the sense of coherence between the surgical group and the non-surgical group.